2017
DOI: 10.1111/appy.12295
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pain and remission in the functioning of patients with depression in Mainland China, Taiwan, and Hong Kong

Abstract: Patients presenting with pain had lower functioning at baseline. At 24 weeks, pain persistence was associated with significantly lower functioning as measured by the Sheehan Disability Scale. Clinical remission was associated with better functional outcomes. The course of pain was related to achieving remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In light of the different study populations and study objectives, we did not believe the aforementioned classification of somatic symptoms to be the optimal somatic symptom grouping strategy for screening depression. Via our unsupervised classification approach, we determined three clusters (energy, vegetative, and other) of somatic symptoms, which were different from the two-dimension (painful and non-painful) or four-dimension (pain, autonomic, energy, and central nervous symptoms) classification in the previous studies ( 19 , 23 , 33 ). Somatic symptoms are heterogeneous that may include different biological entities and require different management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the different study populations and study objectives, we did not believe the aforementioned classification of somatic symptoms to be the optimal somatic symptom grouping strategy for screening depression. Via our unsupervised classification approach, we determined three clusters (energy, vegetative, and other) of somatic symptoms, which were different from the two-dimension (painful and non-painful) or four-dimension (pain, autonomic, energy, and central nervous symptoms) classification in the previous studies ( 19 , 23 , 33 ). Somatic symptoms are heterogeneous that may include different biological entities and require different management.…”
Section: Discussionmentioning
confidence: 99%
“…The total SSI included extensive somatic symptoms which could be interpreted as the total burden of physical symptoms, while the three clusters yielded by clustering analysis represent different domains. The previous studies determined that pain symptoms but not the other dimensions were closely associated with the clinical outcomes of diagnosed MDD ( 23 , 32 , 33 ). Interestingly, in our study, the energy cluster demonstrated superior predictive performance in identifying SD and MDD compared to vegetative and other somatic symptoms.…”
Section: Discussionmentioning
confidence: 99%